Developing Analysis Method of Optimum Portfolio with Value at Risk – Sharia’ Complian Asset Pricing Model (VaR-SCAPM) Approach - Mohammad Farhan Qudratullah (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2017)
Capital Asset Pricing Model (CAPM) in portfolio analysis used the concept of interest rates in the calculation. Interest rates in the concept of Islam financial are forbidden as classified to usury. Therefore, an optimum portfolio analysis tool was developed by replacing the concept of interest rates to zakat rates combined with a Value at Risk analysis tool named Value at Risk–sharia’ Capital Asset Pricing Model (VaR-SCAPM (Z). Its implementation in the sharia’ capital market in Indonesia of January 2011 to August 2016 was obtained by three stocks of Jakarta Islamic Index (JII) of compiler the optimum portfolio of VaR-SCAPM (Z) with proportions 20.71% of KLBF, 38.95% of TLKM, and 40.34% of UNVR. As for the monthly profit rate of 1.75% and the greatest possible loss using VaR-95% of 6.65%.